BOHATER „MAŁEGO REALIZMU” – ZWYKŁY CZŁOWIEK W REPORTAŻACH MAŁGORZATY SZEJNERT („MY, WŁAŚCICIELE TEKSASU”) - Piechota, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents reportage as a form particularly suited to introducing ordinary protagonists, i.e. simple people whose lives become extraordinary thanks to the reporter’s skillful storytelling. In the history of Polish reportage, the school of so-called “little realism” offered particularly interesting portraits of ordinary people, written in opposition to the official socialist propaganda of success. The article also contains analyses of selected pieces from Małgorzata Szejnert’s book, which demonstrate how detailed descriptions of ordinary life in socialism laid bare the manipulation of propaganda.